Consumption smoothing through fiscal policy in OECD and EU countries - Arreaza, Adriana; Sørensen, Bent E.; Yosha, Oved (1998)
We measure the amount of smoothing achieved through various components of the government deficit in EU and OECD countries. For EU countries, at the 1-year frequency percent of shocks to GDP are smoothed via government consumption, 18 percent via transfers percent via subsidies, while taxes provide no smoothing. The results for OECD countries are similar. Government transfers provide more smoothing of negative than of positive shocks among EU countries. There seems to be no trade-off between high government deficits in a country and the ability to smooth consumption. We find that in countries where there is delegation' of power or where fiscal targets are negotiated effectively by coalition members consumption smoothing via government consumption and government transfers is considerably higher. We interpret this finding as evidence that effective budgetary institutions can accomplish efficient consumption smoothing via government deficit spending and lower average deficits.
Keywords: Consommation - Politique publique - Pays de l'OCDE - Modèles économétriques; Consommation - Politique publique - Pays de l'Union eureopéenne - Modèles économétriques; Dépenses publiques - Pays de l'Union européenne - Modèles économétriques; Paiements de tranfert - Pays de l'Union eureopéenne - Modèles économétriques; Paiements de transfert - Pays de l'OCDE - Modèles économétriques; Politik; Ökonometrisches Modell; Consumption (Economics) -- Government policy -- European Union countries -- Econometric models; Consumption (Economics) -- Government policy -- OECD countries -- Econometric models; Deficit financing -- European Union countries -- Econometric models; Deficit financing -- OECD countries -- Econometric models; Expenditures, Public -- European Union countries -- Econometric models; Expenditures, Public -- OECD countries -- Econometric models; Transfer payments -- European Union countries -- Econometric models; Transfer payments -- OECD countries -- Econometric models; Europäische Union. Mitgliedsstaaten